Depressive illness. - Doris, A; Ebmeier, K; Shajahan, P (1999)
WHO estimate that by the beginning of the next century major unipolar depression will be one of the most important causes of ill health overall. Whereas the cause of depression is still obscure, it is becoming clear that a number of diverse factors are likely to be implicated, both genetic and environmental. Effective treatment of depression similarly involves a variety of methods, from electro-convulsive therapy to inter-personal psychotherapy. The pathophysiology of depression is gradually becoming accessible through research strategies, such as functional neuroimaging paired with mood altering interventions.